background image

14.1. SECOND PRODUCT. OBLIQUE PRODUCT

198

Conjecture

1050

.

A ×

RLD

F

B

@

A

n

B

for some filters

A

,

B

.

A stronger conjecture:

Conjecture

1051

.

A ×

RLD

F

B

@

A

n

B

@

A ×

RLD

B

for some filters

A

,

B

.

Particularly, is this formula true for

A

=

B

= ∆

u ↑

R

(0; +

)?

The above conjecture is similar to Fermat Last Theorem as having no value

by itself but being somehow challenging to prove it (not expected to be as hard as

FLT however).

Example

1052

.

A

n

B

@

A ×

RLD

B

for some filters

A

,

B

.

Proof.

It’s enough to prove

A

n

B 6

=

A ×

RLD

B

.

Let ∆

+

= ∆

u ↑

R

(0; +

). Let

A

=

B

= ∆

+

.

Let

K

= (

)

|

R

×

R

.

Obviously

K /

GR(

A ×

RLD

B

).

A

n

B v↑

RLD

(Base(

A

;

B

)

K

and thus

K

GR(

A

n

B

) because

FCD

(Base(

A

;

B

)

K

w

+

×

FCD

Base(

B

)

B

=

FCD

Base(

B

)

B

for

B

= (0; +

).

Thus

A

n

B 6

=

A ×

RLD

B

.

Example

1053

.

A ×

RLD

F

B

@

A ×

RLD

B

for some filters

A

,

B

.

FiXme

: Does it

hold for some principal filters

A

,

B

?

Proof.

This follows from the above example.

Proposition

1054

.

(

A

n

B

)

u

(

A

o

B

) =

A ×

RLD

F

B

for every filters

A

,

B

.

Proof.

(

A

n

B

)

u

(

A

o

B

)

v

l

RLD

f

f

Rel

(Base(

A

); Base(

B

))

,

FCD

f

w A ×

FCD

B

=

l

RLD

f

FCD

f

xyGR(

A ×

FCD

B

)

=

(

RLD

)

out

(

A ×

FCD

B

) =

A ×

RLD

F

B

.

To finish the proof we need to show

A

n

B w A ×

RLD

F

B

and

A

o

B w A ×

RLD

F

B

.

By symmetry it’s enough to show

A

n

B w A ×

RLD

F

B

what is proved above.

Example

1055

.

(

A

n

B

)

t

(

A

o

B

)

@

A ×

RLD

B

for some filters

A

,

B

.

Proof.

(based on [

8

]) Let

A

=

B

= Ω(

N

). It’s enough to prove (

A

n

B

)

t

(

A

o

B

)

6

=

A ×

RLD

B

.

Let

X

∈ A

,

Y

∈ B

that is

X

Ω(

N

),

Y

Ω(

N

).

Removing one element

x

from

X

produces a set

P

. Removing one element

y

from

Y

produces a set

Q

. Obviously

P

Ω(

N

),

Q

Ω(

N

).

Obviously (

P

×

N

)

(

N

×

Q

)

GR((

A

n

B

)

t

(

A

o

B

)).

(

P

×

N

)

(

N

×

Q

)

+

X

×

Y

because (

x

;

y

)

X

×

Y

but (

x

;

y

)

/

(

P

×

N

)

(

N

×

Q

).

Thus (

P

×

N

)

(

N

×

Q

)

/

GR(

A ×

RLD

B

) by properties of filter bases.

Example

1056

.

(

RLD

)

out

(

FCD

)

f

6

=

f

for some convex reloid

f

.

Proof.

Let

f

=

A ×

RLD

B

where

A

and

B

are from example

1053

.

(

FCD

)(

A ×

RLD

B

) =

A ×

FCD

B

by proposition

807

.

So (

RLD

)

out

(

FCD

)(

A ×

RLD

B

) = (

RLD

)

out

(

A ×

FCD

B

) =

A ×

RLD

F

B 6

=

A ×

RLD

B

.